27.7k views
1 vote
Which equations are equivalent to the expression below ? Check all that apply

4^3 * 4^x
A. 4^3 * 4^x
B. (4 * x )^3
C. 4^3-x
D.64 * 4^x
E. 4^3x
F.16^3x

User Weismat
by
5.5k points

1 Answer

5 votes

The given expression is
4^(3) * 4^(x)

By using the law of exponent which states that
a^(m) * a^(n) = a^(m+n)


4^(3) * 4^(x) = 4^(3+x)

We need to find the equivalent expression for the given expression from the given expressions.

1.
4^(3) * 4^(x) = 4^(3+x)

This expression is equivalent to the given expression.

2.
(4 * x)^(3) = (4x)^(3) = 64x^(3)

This expression is not equivalent to the given expression.

3.
4^(3-x)

This expression is not equivalent to the given expression.

4.
64 * 4^(x) = (4)^(3) * 4^(x)=4^(3+x)

This expression is equivalent to the given expression.

5.
4^(3x)

This expression is not equivalent to the given expression.

6.
16^(3x)=(4^(2))^(3x)=4^(6x)

This expression is not equivalent to the given expression.

User Zmaster
by
5.9k points